A Demand-Response Scheme Using Multi-Agent System for Smart DC Microgrid - Diana Severine Rwegasira; Imed Saad Ben Dhaou; Aron Kondoro; Anastasia Anagnostou; Amleset Kelati; Shililiandumi Naiman; Simon JE Taylor; Nerey H Mvungi; Hannu Tenhunen (IGI Global, 2022)
This article describes a framework for load shedding techniques using dynamic pricing and multi-agent system. The islanded microgrid uses solar panels and battery energy management system as a source of energy to serve remote communities who have no access to the grid with a randomized type of power in terms of individual load. The generated framework includes modeling of solar panels, battery storage and loads to optimize the energy usage and reduce the electricity bills. In this work, the loads are classified as critical and non-critical. The agents are designed in a decentralized manner, which includes solar agent, storage agent and load agent. The load shedding experiment of the framework is mapped with the manual operation done at Kisiju village, Pwani, Tanzania. Experiment results show that the use of pricing factor as a demand response makes the microgrid sustainable as it manages to control and monitor its supply and demand, hence, the load being capable of shedding its own appliances when the power supplied is not enough.